Abusive and Enduring Leadership: A Book Review of Keltner, D. (2017). The Power Paradox: How We Gain and Lose Influence. New York, NY: Penguin. Issue 4 (8th February 2019) - Perry, Chad
Abstract : At the University of California Berkeley, Keltner has researched power among social groups in the 21st century. He has claimed that a leader's power is no longer a Machiavellian individual's grab for power over others within a hierarchy; instead, a leader's power is given to him or her by others in the group. However, that power can corrupt many leaders and lead them to become "abusers" of those in their group. In contrast, uncorrupted leaders are "enduring" and remain committed to the greater good of their community. The current review aims to demonstrate how Keltner's book complements the work of other leadership researchers, such as those who study psychopathic leaders, and to investigate its many implications for researchers and leaders.